Analisis Kemampuan Komunikasi Matematis Peserta Didik SD Dalam Menyelesaikan Soal Matematika Ditinjau Dari Kecerdasan Emosional - Lisa Cahyanti; Sarwo Edy (Postulat : Jurnal Inovasi Pendidikan Matematika, 2020)
One of the goals of mathematics is to communicate ideas by using symbols, tables, diagrams, or other media to explain problems or circumstances. Based on the objectives of mathematics learning, the mathematical communication skills of students need to be considered. But many students have difficulty communicating to their mathematical understanding. This is influenced by several factors, one of them is the emotional intelligence of students.This type of research is descriptive with a qualitative approach that aims to describe how students' mathematical communication skills in solving mathematical problems based on the level of emotional intelligence. The subjects of this research are the IVC grade students elementary school of Muhammadiyah Manyar in the academic year 2019 - 2020. This study consists of three students consisting of one student who has high emotional intelligence, one student who has moderate emotional intelligence, and one student who has low emotional intelligence. The methods used in this study are emotional intelligence questionnaire, students' mathematical communication skills test, and interviews. The results of the study indicate that students who have high emotional intelligence have high mathematical communication skills that are also able to illustrate the picture completely, solve coherently and correctly, and provide conclusions correctly. Students with a moderate level of emotional intelligence, have moderate mathematical communication skills, are able to illustrate almost exact and complete images, are able to finish coherently, and are not careful about answers that have been written. Students with low levels of emotional intelligence, have low mathematical communication skills, are able to illustrate almost exact images, find it difficult to write down information that is known and asked, and do not provide conclusions on answers.Keywords: Emotional Intelligence, Mathematical Communication Skills